PERBEDAAN PENGARUH PEMBELAJARAN MENGGUNAKAN MULTIMEDIA INTERAKTIF MODEL DRILLS AND PRACTICE DAN MODEL SIMULATION TERHADAP HASIL BELAJAR MATA PELAJARAN SIMULASI DIGITAL DI SMK N 2 SAWAHLUNTO - Desri Adita; Hanesman Hanesman; Almasri Almasri (Universitas Negeri Padang, 2015)
The problem at this research is laerning outcomes of students at Digital Simulation subject in X TITL SMK N 2 Sawahlunto, which not achieve the baoundary of Minimal Thoroughness Criteria or in Indonesian called KKM. This research purpose in order to know what level of the difference learning outcomes by apply drills and practice learning model and simulation learning model at Digital Simulation subject in X TITL SMK N 2 Sawahlunto school year 2014/2015. This research is an experimental research using quasi experimental method. Interpretation of sampels using non probability sampling technique with purposive sampling, as first experiment class is X TITL 2. This class using drills and practice learning model. Second experiment class is X TITL 1 which use simulation learning model. Datas collection technique from posttests gave every meeting, than this data were analyzed to get normality test, homogenous test and hypothesis test. The result of research in first experimen class get subjection mean 78.79 and second experiment class get subjection mean 70.91. Value of hypothesis test degree of significant α = 0.05 was tcount > ttable (5.3005 > 2.023). It’s mean nil hypothesis (H0) was denied and alternative hypothesis (H1) was received with the difference 8.87 and percentage of different is 12.51%. In conclusion result of analyzed learning outcomes first experiment class and second experiment class, its have significant different of influences between using drills and practice learning model and used simulation learning model. Key Word : learning outcomes, drills and practice learning model, simulation learning model.